Semantic Integration of Uṣūl al-Fiqh Principles in Islamic Family Law: Reconstructing Inheritance Norms through Judicial Practice - Basid, Arhan; Arib, Juhra Muhammad; Sucipto, Imam; Yetta, Yasin; Farhani, Fina (IAIN Manado, 2025)
The determination of Islamic family law relies heavily on accurate semantic construction of Qur’anic and prophetic texts. Although uṣūl al-fiqh provides a comprehensive methodological framework—particularly through the concepts of mutlaq, muqayyad, mujmal, and mubayyan—the application of Islamic inheritance law frequently encounters interpretive inconsistencies that generate judicial disparity and familial conflict. Existing scholarship broadly addresses these semantic principles at a doctrinal level, while insufficiently examining their practical implications within contemporary legal systems. This article addresses that gap by integrating semantic analysis of uṣūl al-fiqh with the empirical realities of Islamic inheritance adjudication in Indonesia. Employing a normative library-based method and a descriptive–analytical approach, the study examines classical and contemporary uṣūl al-fiqh literature alongside statutory instruments and judicial precedents of the Religious Courts and the Supreme Court. The findings demonstrate that semantic principles function not merely as linguistic classifications but as epistemic tools that shape legal reasoning, guide judicial clarification of indeterminate norms, and align inheritance rulings with the objectives of Islamic law (maqāṣid al-sharīʿah), particularly the protection of wealth and family integrity. By mapping the interaction between semantic rules, legal objectives, and judicial practice, this study contributes a contextualized interpretive model that preserves textual validity while enhancing substantive justice in Islamic family law.